IBNU RUSYD: (PEMBELAAN TERHADAP PARA FILOSOF) - Dr. Zainuddin Hamkah (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
Ibn Rushd responds to al-Ghazali's accusation of infidelity of Islamic philosophers on three points: First, natural mood, second, physical resurrection does not exist, and the three divine knowledge is only kulliy. Ibn Rushd asserts that al-Ghazali has misunderstood the philosopher. There is no Muslim philosopher who thinks so. Ibn Rushd rectifies that the philosopher's opinion that God's knowledge of the details (juz'iyyat) is different from that of human knowledge. Human knowledge is to take the form of effect or through the five senses, while the knowledge of God is the cause for the realization of such details. Therefore humanknowledge is new and God's knowledge is qadim. God knows everything that happens in nature. However, the knowledge of God can not be given sifa-properties juz'iyyat or kulliyat, because such properties can only be attributed to beings only. Certainly God's knowledge can only be known by God himself. These three problems, because there is no Qur'anic texts or hadith of the Prophet Muhammad. That affirms it, then it requires human creative thinking to understand it. In principle all Muslims recognize the creation of nature by Allah, the attentive nature of Allah and the resurrection of man in the hereafter. It's just that they differ in interpretative and technical matters. It is therefore inappropriate for them to disbelieve each other, because their opinions do not contradict the opinions of Muslims in general.